Emergency Hemorrhage Panel Implementation Decreases Rotational Thromboelastometry (ROTEM) Use for Transfusion Decisional Support. (21st September 2018) - Tokuda, Nathan H; Richards, Cheryl; Lockhart, Evelyn; Crookston, Kendall P
Abstract: Objectives: Rotational thromboelastometry (ROTEM) is a viscoelastic point-of-care coagulation assay that provides an overall assessment of the hemostatic system with rapid turnaround times (TATs). The availability and timeliness of the information provided by ROTEM are useful in transfusion decisional support to help achieve hemostasis in actively bleeding patients. However, point-of-care tests such as ROTEM suffer from drawbacks such as lower accuracy, errors in predicting the need for transfusion, and performance by staff without laboratory training. Similar and equally timely data may be obtained more economically via an emergency hemorrhage panel (EHP). An EHP is a panel of standard hematology and coagulation tests, performed in a clinical laboratory on automated instruments, optimized for rapid TAT. Whether ROTEM use decreases after institutional EHP implementation remains to be determined. Methods: ROTEM has been available at our institution since February 2013. Our EHP, implemented in August 2016, consists of the following laboratory tests: hemoglobin, platelet count, prothrombin time/international normalized ratio (INR), and fibrinogen level. The laboratory target TAT for the EHP is 15 minutes or less from laboratory acceptance of the sample. Informative sessions were held to educate providers about the EHP following laboratory implementation. The monthly number of ROTEM tests performed from January 2016 through November 2017, and the monthly number of EHPs performed from August 2016 through November 2017, was collected. Data from August 2016 were omitted from analysis to eliminate ROTEM and ROTEM/EHP availability timeframe overlap as a source of error. Based on reagent, quality control, and labor costs, estimates of 67.00 USD per ROTEM and 2.22 USD per EHP were used to estimate laboratory testing costs. Results: A total of 1, 435 ROTEM tests were performed from January 2016 through July 2016, resulting in a monthly median of 197 ROTEM tests with a median monthly cost of $13, 199. From September 2016 through November 2017, 1, 060 ROTEM tests were performed, resulting in a monthly median of 65 ROTEM tests with a median cost of $4, 355. From September 2016 through November 2017, 2, 795 EHPs were performed, resulting in a monthly median of 141 EHPs with a median monthly cost of $313. Therefore, after EHP implementation, the median monthly number of ROTEM tests decreased by 67%, decreasing the median monthly ROTEM cost by $8, 844. The median monthly cost of both EHP and ROTEM was $4, 668, resulting in a median monthly savings of $8, 534 (65%) when compared to ROTEM-only availability. Conclusions: ROTEM utilization decreases after implementation of an EHP for transfusion decisional support. A corresponding reduction in laboratory testing costs is observed. The effect of EHP implementation on blood product utilization requires further investigation.